Hak Sipil dan Politik Kaum Marginal: Upaya dan Perjuangan Kelompok Transpuan di Kota Pangkalpinang - Embun Balqis, Fabiancha (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The purpose of this study is to describe how the Civil and Political Rights of the Transpuan group in Pangkalpinang City fulfill the Civil and Political Rights and to describe the efforts made by the group in fighting for civil and political rights as citizens. The primary data sources used were observations and in-depth interviews with Transpuan in Pangkalpinang City regarding the class struggle of the Transpuan group in Pangkalpinang City as marginal groups. At the same time, the secondary data are books, journals, theses from previous research, and internet sources relevant and related to the research focus. The research subjects who will be informants are Transpuan in Pangkalpinang City, Transpuan from Pangkalpinang City and its surroundings, and Transpuan from outside the Bangka Belitung Islands Province. The results of this study state that the fulfillment of the civil rights of Transpuan in Pangkalpinang City by the government has not been fully implemented.